The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1103/physrevd.101.083002
|View full text |Cite
|
Sign up to set email alerts
|

Precursor flares of short gamma-ray bursts from crust yielding due to tidal resonances in coalescing binaries of rotating, magnetized neutron stars

Abstract: As evidenced by the coincident detections of GW170817 and GRB 170817A, short gamma-ray bursts are likely associated with neutron star-neutron star merger events. Although rare, some bursts display episodes of early emission, with precursor flares being observed up to ∼ 10 seconds prior to the main burst. As the stars inspiral due to gravitational wave emission, the exertion of mutual tidal forces leads to the excitation of stellar oscillation modes, which may come into resonance with the orbital motion. Mode a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 120 publications
(246 reference statements)
0
11
0
Order By: Relevance
“…It has been suggested that the crust breaking strain is around 0.1 [74], which corresponds to a critical ellipticity of c ≈ δR/R ≈ 4 × 10 −6 , where R + δR is the elongated NS radius. This can be easily reached by the tidally-induced f-mode oscillation in the last seconds before the merger [65] (see also Figure 3 of Reference [75]). Recent works show that the g-mode can also lead to the breaking of the NS crust [66].…”
Section: Ns Crust Crack Modelmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been suggested that the crust breaking strain is around 0.1 [74], which corresponds to a critical ellipticity of c ≈ δR/R ≈ 4 × 10 −6 , where R + δR is the elongated NS radius. This can be easily reached by the tidally-induced f-mode oscillation in the last seconds before the merger [65] (see also Figure 3 of Reference [75]). Recent works show that the g-mode can also lead to the breaking of the NS crust [66].…”
Section: Ns Crust Crack Modelmentioning
confidence: 95%
“…Besides, there are two more scenarios proposed only for SGRB precursors. During the inspiral phase of the NS-NS/black hole (BH) binary, the magnetospheric interaction of the binary [55][56][57][58][59][60][61][62][63], or the crust crack of the NS [64][65][66] may also generate gamma-ray emissions. As such, precursors of SGRBs may shed light on the physical processes right before or shortly after the merger.…”
Section: Introductionmentioning
confidence: 99%
“…The different oscillation patterns of a neutron star are characterized by their restoring force, e.g., p(pressure)-modes, g(gravity)-modes, i(Coriolis)-modes, s(shear)-modes or w(wave)modes. The f-mode is the fundamental mode of the p-mode sequence and it is the oscillation mode most likely to be excited in violent processes such as neutron star formation by supernova core collapse (Torres-Forné et al (2018;), the pre-merger interaction of neutron stars (see, e.g., Lai (1994); Kokkotas and Schafer (1995); Fuller and Lai (2011); Gold et al (2012); Chirenti et al (2017); Chaurasia et al (2018); Suvorov and Kokkotas (2020); Kuan et al (2021a,b)), the early-post-merger oscillations of the final object (Shibata and Taniguchi (2006); Bauswein and Janka (2012); Hotokezaka et al (2013); Bernuzzi et al (2014); Bauswein et al (2014); Lehner et al (2016); Bauswein et al (2017); Rezzolla and Takami (2016); Takami et al (2015); De Pietri et al (2018); Breschi et al (2019)). In the case that the merging neutron stars are of relatively small mass and the postmerger object is a fast spinning neutron star, the unstable f-mode oscillations can lead to its spin-down ).…”
Section: Asteroseismologymentioning
confidence: 99%
“…The different oscillation patterns of a neutron star are characterized by their restoring force, e.g., p(pressure)-modes, g(gravity)-modes, i(Coriolis)-modes, s(shear)-modes or w(wave)modes. The f -mode is the fundamental mode of the p-mode sequence and it is the oscillation mode most likely to be excited in violent processes such as neutron star formation by supernova core collapse ( [20,21]), the pre-merger interaction of neutron stars (see, e.g., [22][23][24][25][26][27][28][29][30]), the early-post-merger oscillations of the final object ( [31][32][33][34][35][36][37][38][39][40][41]). In the case that the merging neutron stars are of relatively small mass and the post-merger object is a fast spinning neutron star, the unstable f -mode oscillations can lead to its spin-down ( [42]).…”
Section: A Asteroseismologymentioning
confidence: 99%